1985
DOI: 10.3354/meps025189
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Coenobita scaevola (Forskal) (Crustacea, Anemura) to terrestrial life in desert-bordered shore line

Abstract: Coenobita scaevola (Forskal) is a terrestrial hermit crab inhabiting shores of the S~n a i Peninsula, where animals encounter severe conditions of high temperature, high radiation and low relative humidity. Adaptation of these crabs to such arid conditions was studied. The crabs are nocturnally active, taking refuge during the day in hiding places with milder conditions. Body temperature follows that of their hiding places, which is lower than that of the air. After ca 6 h exposure to direct radiation, the cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Coenobita violascens preferentially occupied shells of one gastropod species, as also noted earlier in other land hermit crabs (Sripathi et al, 1977;Abrams, 1978;Achituv and Ziskind, 1985;Guillen and Osorno, 1993;Walker, 1994;Barnes, 1999;Morrison and Spiller, 2006;Sallam et al, 2008;Laidre and Vermeij, 2012;Bundhitwongrut et al, 2015). The different proportions of occupied shell species may infer active behavior of C. violascens in shell selection (Sallam et al, 2008;Bundhitwongrut et al, 2015).…”
Section: Discussionsupporting
confidence: 48%
“…Coenobita violascens preferentially occupied shells of one gastropod species, as also noted earlier in other land hermit crabs (Sripathi et al, 1977;Abrams, 1978;Achituv and Ziskind, 1985;Guillen and Osorno, 1993;Walker, 1994;Barnes, 1999;Morrison and Spiller, 2006;Sallam et al, 2008;Laidre and Vermeij, 2012;Bundhitwongrut et al, 2015). The different proportions of occupied shell species may infer active behavior of C. violascens in shell selection (Sallam et al, 2008;Bundhitwongrut et al, 2015).…”
Section: Discussionsupporting
confidence: 48%
“…The land hermit crab is very abundant above the sea levels on the beaches of the Red Sea and the highly arid shores of Sinai Peninsula, but is totally dependent on the sea for water and consequently limited to the near shore area (Achituv and Ziskind, 1985). In the present study the maximum abundance of Coenobita scaevola was found in supra-littoral zone among four investigated zones.…”
Section: Discussionsupporting
confidence: 40%
“…This semi-terrestrial species is very abundant above the sea level on the beaches of the Red Sea and the highly arid shores of Sinai Peninsula, but is totally dependent on the sea for water and consequently limited to the nearshore area (Achituv and Ziskind, 1985). Coenobita scaevola is the only species representing the family Coenobitidae inhabiting the Red Sea (Sallam et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The gills of Coenobita are also markedly reduced (Harms, 1932) and weight specific gill area of C. scaevola (expressed per unit live weight) is of the same order as for B. latro (Achituv and Ziskind, 1985). However, the mollusc shells in which hermit crabs live physically constrain development of branchiostegal lungs.…”
Section: Gas Exchangementioning
confidence: 99%
“…These authors suggested that Coenobita might retain aquatic respiratory patterns by circulation of shell water over the gills but there are no behavioural or physiological data that support this. The animals will commonly encounter elevated PCO 2 both while retracted into the shell for long periods and when buried in the sand during diurnal periods of inactivity (Vannini, 1975b;Achituv and Ziskind, 1985). An alternate explanation for their insensitivity to CO 2 may be that it is an adaptation to high environmental CO 2 (common in burrow-dwelling animals) rather than retention of "aquatic" gas exchange.…”
Section: Gas Exchangementioning
confidence: 99%